JURIDICAL STUDY OF THE APPLICATION OF LAW NUMBER 18 OF 2012 CONCERNING FOOD (STUDY: TRADITIONAL ALCOHOLIC BEVERAGE BUSINESS ACTORS IN KAMBANIRU VILLAGE, EAST SUMBA-NTT REGENCY) - Huky Leba , Hendro; Saverius Nurdin, Fransiskus (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
This study aims to analyze the extent to which the effectiveness of the application of Law No. 18 of 2012 concerning Food to business actors producing traditional alcoholic beverages in Kambaniru Village. The type of research used is empirical normative the analytical-descriptive research uses a statutory approach and a conceptual approach. The results of the study show that Law number 18 of 2012 concerning Food is not implemented by business actors producing traditional alcoholic beverages in the Kambaniru village because production business actors do not know the A quo law and the manufacturing process is still a simple way and the equipment is not following the provisions normative rules.